Early and Late-Phase 24 h Responses of Stored Red Blood Cells to Recipient-Mimicking Conditions - Tzounakas, Vassilis L.; Anastasiadi, Alkmini T.; Karadimas, Dimitrios G.; Velentzas, Athanassios D.; Anastasopoulou, Violetta I.; Papageorgiou, Effie G.; Stamoulis, Konstantinos; Papassideri, Issidora S.; Kriebardis, Anastasios G.; Antonelou, Marianna H. (Frontiers in Physiology, 2022)
The 24-hour (24 h) post-transfusion survival of donor red blood cells (RBCs) is an important marker of transfusion efficacy. Nonetheless, within that period, donated RBCs may encounter challenges able to evoke rapid stress-responses. The aim of the present study was to assess the effect of exposure to plasma and body temperature upon stored RBCs under recipient-mimicking conditions in vitro from the first hours “post-transfusion” up to 24 h. For this purpose, packed RBCs from seven leukoreduced CPD/SAGM units were reconstituted with plasma of twenty-seven healthy individuals and incubated for 24 h at 37oC. Three units were additionally used to examine stress-responses in 3-hour intervals post mixing with plasma (n = 5) until 24 h. All experiments were performed in shortly-, medium-, and long-stored RBCs. Hemolysis, redox, morphology, membrane protein binding and vesiculation parameters were assessed. Even though spontaneous hemolysis was minimal post-reconstitution, it presented a time-dependent increase. A similar time-course profile was evident for the concentration of procoagulant extracellular vesicles and the osmotic fragility (shortly-stored RBCs). On the contrary, mechanical fragility and reactive oxygen species accumulation were characterized by increases in medium-stored RBCs, evident even from the first hours in the recipient-mimicking environment. Finally, exposure to plasma resulted in rapid improvement of morphology, especially in medium-stored RBCs. Overall, some RBC properties vary significantly during the first 24 h post-mixing, at levels different from both the storage ones and the standard end-of-24 h. Such findings may be useful for understanding the performance of RBCs and their possible clinical effects −especially on susceptible recipients− during the first hours post-transfusion.